Effect of adding titanium dioxide nanoparticles on anti-microbial activity and surface detail reproduction of dental alginate - Omer , Ranj A.; Abdel-Rahman, Hoshang Kh.; Saleh, Mahabad M.; Al-Hawezi, Sazgar S.Q.; Ikram, Fahd S. (Journal of Baghdad College of Dentistry, 2023)
Most dental works require a diagnostic impression; alginate is contemplated as the most popular material used for this purpose. Titanium dioxide nanoparticles show evidence of antimicrobial activity in the recent era, for this purpose, this study aimed to evaluate the effect of adding Titanium dioxide nanoparticles on antimicrobial activity and surface detail reproduction of alginate impression material. Materials and methods: Titanium dioxide nanoparticles (purity = 99%, size= 20nm) was added to alginate at three different concentrations (2%, 3% and 5%). 84 samples were prepared in total. Samples were tested for antimicrobial activity using a disc diffusion test, and surface detail reproduction was done using (ISO 21563:2021). One-way ANOVA and independent sample t-test were used for data analysis through SPSS software. Results: for the antimicrobial test, inhibition zones for Streptococcus mutans and Candida albicans showed significant changes concerning the alteration in Titanium dioxide nanoparticle concentrations. The inhibition zone significantly increased with an increase in the percentage of Titanium dioxide nanoparticles. The mean of the inhibition zone for S. mutans was superior to C. albicans and the difference was statistically significant. Regarding surface detail reproduction, the control group, 2% and 3% groups manifested very similar results, only the group to which 5% of Titanium dioxide nanoparticles were added showed a decline in detail reproduction when compared to the other three groups. Conclusion: Within the limitation of this study, we can conclude that the antimicrobial activity against S mutans and C. albicans were significantly increased in modified groups, and this escalation was directly linked to the increase in Titanium dioxide nanoparticles concentration. In contrast, the surface detail reproduction was decreased when adding 5% Titanium dioxide nanoparticles to alginate.